Implementation of Moral Education Values at the Integrated Islamic Primary School (SDIT) Mutiara Kebonan, Karanggede District Boyolali Regency - Arifin; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to find out more deeply about the implementation of moral education values at the Mutiara Kebonan integrated Islamic elementary school. This research is a qualitativeresearch. The subjects of this research were school principals, school management, PAI teachers and students. Data was obtained through observation, structured interviews and documentation as well as relevant literature results. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of moral education values is through advice, example, attention and habituation. Meanwhile, the moral education values applied are the Value of Moral Education towards Allah SWT, the Value of Moral Education towards the Prophet Muhammad SAW and the Value of Moral Education towards the Family.